2014
DOI: 10.1016/j.nlm.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal single-unit firing associated with deficient extinction in mice

Abstract: The neural circuitry mediating fear extinction has been increasingly well studied and delineated. The rodent infralimbic subregion (IL) of the ventromedial prefrontal cortex (vmPFC) has been found to promote extinction, whereas the prelimbic cortex (PL) demonstrates an opposing, pro-fear, function. Studies employing in vivo electrophysiological recordings have observed that while increased IL single-unit firing and bursting predicts robust extinction retrieval, increased PL firing can correlate with sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 58 publications
2
59
1
Order By: Relevance
“…Neurons in both IL and PL exhibited much more dramatic changes in spontaneous firing immediately after CS-US pairings on day 1 than after presentation of the CS alone on day 2, despite similar (and nearly asymptotic) levels of freezing behavior in each session, particularly in vehicle-treated rats. These results indicate that it is not high levels of fear per se that correlate with changes in mPFC neuronal firing (23,24,(32)(33)(34), but rather the emotional context in which that fear is experienced (46,47). Specifically, our results suggest that mPFC firing is particularly sensitive to the acute effects of the footshock US, possibly reflecting unconditioned components of fear in the immediate aftermath of shock exposure.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Neurons in both IL and PL exhibited much more dramatic changes in spontaneous firing immediately after CS-US pairings on day 1 than after presentation of the CS alone on day 2, despite similar (and nearly asymptotic) levels of freezing behavior in each session, particularly in vehicle-treated rats. These results indicate that it is not high levels of fear per se that correlate with changes in mPFC neuronal firing (23,24,(32)(33)(34), but rather the emotional context in which that fear is experienced (46,47). Specifically, our results suggest that mPFC firing is particularly sensitive to the acute effects of the footshock US, possibly reflecting unconditioned components of fear in the immediate aftermath of shock exposure.…”
Section: Discussionmentioning
confidence: 60%
“…It has previously been suggested that stress-induced changes in prefrontal cortical structure and function observed in animal models may contribute to the extinction deficits observed in patients with PTSD (22)(23)(24). Given the abundant literature implicating NE signaling in prefrontal cortical function (25,26), it is conceivable that stress-induced elevations in prefrontal NE release (27)(28)(29) contribute to extinction impairments associated with PTSD.…”
mentioning
confidence: 99%
“…The robust effects of CIE on ILC neurons as compared to PLC neurons in mice may be related to their differing connectivity and roles in several behaviors mediated by the PFC (Fitzgerald et al, 2014; Holmes et al, 2012). For example, while PLC activation promotes fear behavior, ILC neuronal activity promotes extinction (Fitzgerald et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, while PLC activation promotes fear behavior, ILC neuronal activity promotes extinction (Fitzgerald et al, 2014). We have previously shown that CIE impairs fear extinction mediated by a reduction in NMDA receptor-dependent burst firing of ILC, but not PLC, neurons (Holmes et al, 2012), and we have also observed a decrease in expression of the neuroactive steroid 3α-hydroxy-5α-pregnan-20-one (3α,5α-THP), a positive allosteric modulator of GABA A receptors, in the PFC (Maldonado-Devincci et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most BA neurons show sustained responses that last for the entire CS duration and in some cases beyond, mirroring the persistence of conditioned fear responses (Amano et al, 2011). Interestingly, prelimbic (PL) neurons show a similar response pattern (Burgos-Robles et al, 2009; Fitzgerald et al, 2013; Courtin et al, 2014). Moreover, PL inactivation impairs fear expression (Corcoran and Quirk, 2007), and BLA inactivation abolishes tone responses in PL (Sotres-Bayon et al, 2012).…”
Section: Acquisition and Expression Of Conditioned Fearmentioning
confidence: 99%